2005
DOI: 10.1079/phn2005786
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of stunting and overweight in 3-year-old black South African children residing in the Central Region of Limpopo Province, South Africa

Abstract: Objectives: To determine the prevalence of stunting, wasting and overweight and their determinants in 3-year-old children in the Central Region of Limpopo Province, South Africa. Design: Prospective cohort study. Setting: Rural villages in the Central Region of the Limpopo Province, South Africa. Subjects: One hundred and sixty-two children who were followed from birth were included in the study. Anthropometric measurements and sociodemographic characteristics of the children were recorded. Results: Height-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
151
8
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(191 citation statements)
references
References 42 publications
(56 reference statements)
26
151
8
6
Order By: Relevance
“…A recent Prospective Urban and Rural Epidemiology (PURE) study has shown that poor health outcomes are significantly associated with a high CHO intake. Also, the level of stunting is high (48%) [22]. The high level of CHO intake could be linked to food insecurity in a low SES setting, thus greater reliance on cheap, refined foodstuffs (SSB, white bread, mealie-meal, sugar).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Prospective Urban and Rural Epidemiology (PURE) study has shown that poor health outcomes are significantly associated with a high CHO intake. Also, the level of stunting is high (48%) [22]. The high level of CHO intake could be linked to food insecurity in a low SES setting, thus greater reliance on cheap, refined foodstuffs (SSB, white bread, mealie-meal, sugar).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies from the DHDSS site were fragmented and considered only diet or physical activity (PA) [15,21,22], while this study considers the relationship of socio-demographic, lifestyle and biological factors with BMI through a sex-specific, hierarchical multiple linear regression modelling approach. Consequently, this study provides baseline DHDSS site cohort data for Phase 2 of the Africa Wits-INDEPTH (International Network for the Demographic Evaluation of Populations and Their Health) partnership for Genomic (AWI-Gen) Study.…”
Section: Introductionmentioning
confidence: 99%
“…Body mass for rural areas in South Africa have been reported in various nutritional studies (Cameron and Kgamphe, 1993;Mamabolo et al, 2004Mamabolo et al, , 2005Monyeki et al, 2000;Mostert et al, 2005;Nel and Steyn, 2002;Steyn et al, 1992). For the PK model, we linearly interpolated the data to obtain a growth curve for a woman (see Supplemental Material, Figure S1).…”
Section: Calculation Of Total Ddt Concentration In Womenmentioning
confidence: 90%
“…In the first five years of life, the double burden of under- and over-nutrition in South Africa is evident [31,32]. In 2013, 22.9% of 2–5-year-old children were reported to be overweight or obese, and the prevalence of stunting was 21.5%.…”
Section: Nutrition and Physical Activity During Infancy And Childhoodmentioning
confidence: 99%
“…However in children 0–3 years, the prevalences of stunting were as high as 26.9% for boys and 25.9% for girls [33]. An earlier study showed that the co-prevalence of stunting and overweight in 3-year-old children was 19% [32]. Research in LMICs suggests that stunted children have impaired lipid metabolism favouring the accumulation of adipose tissue, and that in the context of high energy intake and low energy expenditure, undernourished children could be at risk for developing overweight/obesity [3436].…”
Section: Nutrition and Physical Activity During Infancy And Childhoodmentioning
confidence: 99%